Effects of a Parity-Violating Interaction in an Exactly Soluble Model - Hernández, Esteban (1972)
The concept of a parity-mixed intrinsic shape and its consequences have received a great deal of attention. In particular, a detailed and extensive investigation of parity-mixed Hart ree-Fock (HF) solutions was carried out by several authors (1-3). The tensor part of the nuclear force was considered to be the main cause for the existence of these solutions (2-3). Recently, PACATI and BOFFI (4) have carefully investigated the advantages of the projection-before-variation (PBV) method. Their study was made in connection with the par i ty projection (PP) from a Slater determinant built with single-particle (s.p.) orbitals without define parity . They made a comparison between the PBV results and those arising from the conventional projection-after-variation (PAV) procedure. An elegant PBV solution is found in ref. (4), involving a set of coupled nonlinear equations. In practice, they are very difficult to treat from the computational point of view, so the above-mentioned authors performed a direct minimization on the expression for the projected energy. A considerable gain in binding energy is obtained in that way although the great number of parameters needed limited their study to 8H and 3He. The present authors feel that the subject is interesting enough so as to justify the study of the parity-mixing problem withing the context of an exactly soluble model. In this case it is possible to solve the PBV equations without recourse to parametrizations, and in addition, there is an exact solution which allows one on judge on thet of the PBV approach in relation to the PAV one.